Integrasi Sistem Informasi Manajemen Dan Teknologi GIS Untuk Pengelolaan Data Di Rumah Tahfidz Al-Ma’arif Banjarmasin - Mariatul Kiftiah; Arifin Noor Asyikin; Fuad Sholihin; Subandi (Prosiding SISFOTEK, 2025)
Effective data management plays a crucial role in improving administrative efficiency in educational institutions, including Rumah Tahfidz. Rumah Tahfidz Al-Ma’arif Banjarmasin, as a non-formal educational institution, requires a system capable of systematically recording, monitoring, and visualizing data. This study aims to develop a web-based management information system integrated with Geographic Information System (GIS) technology to support data management in the institution. The system development follows the Waterfall method, which consists of sequential stages: planning, requirements analysis, design, implementation, testing, and maintenance. This approach was chosen because it provides a structured workflow, ensuring that the system is developed according to user needs. The system is built using the Laravel framework and Filament for the admin interface, and is equipped with an interactive GIS-based map to display the distribution locations of donation boxes. It also implements a role and permission management system with four user levels: admin, teacher, volunteer, and owner, to ensure secure and efficient access. Black-box testing shows that all features function as expected. An evaluation using the System Usability Scale (SUS) with 33 respondents resulted in a score of 74.55, indicating good usability. The results show that this system effectively supports data management, information transparency, and administrative decision-making.